2013
DOI: 10.1186/1471-2091-14-23
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved arginine residue of the chitosanase from Streptomyces sp. N174 is involved both in catalysis and substrate binding

Abstract: BackgroundStreptomyces sp. N174 chitosanase (CsnN174), a member of glycoside hydrolases family 46, is one of the most extensively studied chitosanases. Previous studies allowed identifying several key residues of this inverting enzyme, such as the two catalytic carboxylic amino acids as well as residues that are involved in substrate binding. In spite of the progress in understanding the catalytic mechanism of this chitosanase, the function of some residues highly conserved throughout GH46 family has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
2
8
1
Order By: Relevance
“…The −2 subsite is one of the most important determinants of the specificity of OU01 enzyme as a chitosanase, where the substrate interacts with two highly conserved residues: Arg 45 and Asp 60 . This observation confirmed previous studies by site-directed mutagenesis, which showed that mutations of corresponding residues in other chitosanases resulted in severe impairment of enzymatic activity [ 49 , 55 , 57 ]. Performing a series of mutations of residues in the substrate-binding cleft, Lyu et al concluded that, “the subsites −2, −1 and +1 are probably the dominant contributors for substrate binding and essential for hydrolysis” [ 33 ].…”
Section: Structure–function Relationships: Summary Of Results Fromsupporting
confidence: 92%
See 1 more Smart Citation
“…The −2 subsite is one of the most important determinants of the specificity of OU01 enzyme as a chitosanase, where the substrate interacts with two highly conserved residues: Arg 45 and Asp 60 . This observation confirmed previous studies by site-directed mutagenesis, which showed that mutations of corresponding residues in other chitosanases resulted in severe impairment of enzymatic activity [ 49 , 55 , 57 ]. Performing a series of mutations of residues in the substrate-binding cleft, Lyu et al concluded that, “the subsites −2, −1 and +1 are probably the dominant contributors for substrate binding and essential for hydrolysis” [ 33 ].…”
Section: Structure–function Relationships: Summary Of Results Fromsupporting
confidence: 92%
“…OU01 chitosanase; Glu 37 in Bacillus circulans MH-K1 chitosanase; Figure 3 a,b). Then, the amino acid chain traverses the substrate binding cleft, goes into the minor lobe and forms a series of three short β-sheets and intercalating loops, accommodating several residues essential for catalysis: the aspartate which functions as a general base (Asp 43 and Asp 55 , respectively; Figure 3 a,b), a threonine (Thr 48 and Thr 60 ) orientating a water molecule for nucleophilic attack and an arginine (Arg 45 and Arg 57 ) hydrogen bound to the general base aspartate and thought to optimize its function, besides interacting with the substrate [ 49 ] ( Figure 3 a,b). These three residues are strictly conserved in chitosanases which enzymatic activity is experimentally confirmed, with the exception of the enzyme marked as Cho4239-1_Jan on Figure 1 , originating from Janthinobacterium sp.…”
Section: Structure–function Relationships: Summary Of Results Frommentioning
confidence: 99%
“…Mutations of Ile42 to either positively charged (Lys, Arg, and His) or negatively charged (Asp and Glu) residues led to a decrease in specific activity and an increase in thermal stability, respectively (Table 2). Thus, our data show a different effect on catalytic activity than the previous report, which showed that the presence of a positive charge near the catalytic nucleophile glutamate resulted in an increase in k cat (Lacombe-Harvey et al, 2013).…”
Section: Structural Localization Of Ile42contrasting
confidence: 99%
“…It is now generally recognized that some residues in the catalytic cleft of glycoside hydrolases, other than the catalytic residues, might play an essential role in catalytic activity. Such residues can be involved not only in enzyme-substrate interactions or structure stabilization, but also in the creation of interaction networks essential for catalysis (Lacombe-Harvey et al, 2013). As a previous study has indicated that the stabilizing AA substitutions are positioned in loops on the periphery of the active domain TIM barrel (Höcker, 2005), we suggest that Ile42 is influencing the catalytic nucleophile residue and the thermostability of the enzyme by optimizing structural interactions.…”
Section: Structural Localization Of Ile42mentioning
confidence: 75%
“…It was shown previously that the specific activity of chitosanases can vary according to the DDA of chitosan and that a single mutation could alter the substrate preference profile (Shimosaka et al 1995 ; Lacombe-Harvey et al 2013 ). Here, we tested two chitosans with DDA of 84.6 and 98.4%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%